Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

​​​Shown below are the steps used to solve an equation.
5 - 3 (x - 1) = 4 - 7x
5 - 3x + 3 = 4 - 7x
8 - 3x = 4 - 7x
8 = 4 - 4x
x= -1
​Explain what is happening to the equation during each step in the solution.